SEMERU BANGKIT: MOTIVASI MENUMBUHKAN SEMANGAT DAN PENYALURAN BANTUAN SOSIAL PENGUNGSI SEMERU DI LUMAJANG JAWA TIMUR (PKM NASIONAL ASOSIASI DOSEN AKUNTANSI INDONESIA) - Antin Okfitasari; Devi Narulitasari; Arfan Ikhsan; Edy Supriyono (LPPM ITB AAS Indonesia Surakarta, 2023)
The eruption of Semeru is an unexpected disaster without any signs of nature. Mount Semeru emits thick hot clouds. The areas that were quite badly affected by the disaster were Supiturang Village, Curah Kobokan Village and Sumberwuluh Village, Lumajang, East Java. The consequences of this disaster resulted in casualties and thousands of residents being displaced. Deep grief and unsupportive situations should be a factor in the economic and social paralysis of the people affected by the disaster. The partners of this PKM are the residents of the three villages that were most affected by the disaster. The aim of this PKM is for partners to grow enthusiasm to bounce back after a disaster and distribute social assistance to ease the burden on residents affected by the disaster. This national PKM is conducted by accounting lecturers who are members of ADAI. Refugees feel very happy and motivated again to get out of the downturn caused by the disaster. They were very enthusiastic and grateful for the assistance provided in this PKM. The output of science and technology that has been achieved is a change in the attitude of residents affected by disasters from apathy to enthusiasm to get up and a sense of optimism to improve and be prepared if disaster comes again